PENGARUH PEMBERIAN ALAT PERMAINAN EDUKATIF PADA ANAK USIA TODDLER (1-3 TAHUN) TERHADAP PERKEMBANGAN ANAK DI DESA MOJOWANGIÂ KECAMATANÂ MOJOWARNO KABUPATEN JOMBANGÂ - Ratnaningsih, Tri; Zainuri, Imam (JURNAL KEPERAWATAN SEHAT, 2012)
Currently the community is still found children who can not use age-appropriate games, toddler age children should have been able to use these games so that children can not develop according to his age. Thats why there are still many children who experience delays in the development. The purpose of this study to analyze the Effect of Tool on Childhood Educational Games Toddler (1-3 Years) Against Child Development in the Village District MojowangiMojowarnoJombang District. The method used in this study is an analytical study is an observational analytic, with a